PENGGGUNAAN SIDIK JARI DALAM PEMBUKTIAN TINDAK PIDANA PEMBUNUHAN PADA TAHAP PENYIDIKAN (Studi Kasus di Polrestabes Makassar): THE USE OF FINGERPRINTING IN PROVISION OF THE CRIME OF MURDER IN THE STAGE OF THE INVESTIGATION (Case Study at Polrestabes Makassar) - Adang, Chiep Panji; Oner, Basri (Clavia, 2021)
This study aims to determine the process of using fingerprints in proving a murder crime at the investigation stage and to determine the constraints in the use of fingerprints in proving a murder crime at the investigation stage. This research uses descriptive analysis type of research that uses empirical juridical research type. This study states that fingerprints (dactyloscopy) are used as evidence in uncovering murder crime cases in order to find suspects, fingerprints are also very effective and have advantages, the obstacles encountered in using fingerprints in proving murder crimes at the investigation stage, are resource constraints human resources, few members of the police who have expertise in the field of ductyloscopy, weather, facilities in the field of fingerprints and the community will lack knowledge of the crime scene.